Improved Conventional and New Approaches in the Diagnosis of Tuberculosis - Dong, Baoyu; He, Zhiqun; Li, Yuqing; Xu, Xinyue; Wang, Chuan; Zeng, Jumei (Frontiers in Microbiology, 2022)
Tuberculosis (TB) is a life-threatening infectious disease caused by Mycobacterium tuberculosis (M. tuberculosis). Timely diagnosis and effective treatment are essential in the control of TB. Conventional smear microscopy still has low sensitivity and is unable to reveal the drug resistance of this bacterium. The traditional culture-based diagnosis is time-consuming, since usually the results are available after 3 to 4 weeks. Molecular biology methods fail to differentiate live from dead M. tuberculosis, while diagnostic immunology methods fail to distinguish active from latent TB. In view of these limitations of the existing detection techniques, in addition to the continuous emergence of multidrug-resistant and extensively drug-resistant TB, in recent years there has been an increase in the demand for simple, rapid, accurate and economical point-of-care approaches. This review describes the development, evaluation and implementation of conventional diagnostic methods for TB and the rapid new approaches for the detection of M. tuberculosis.